TRADITIONAL GAMES "GIM-GIMAN" FOR CHARACTER STRENGTHENING OF ELEMENTARY SCHOOL STUDENTS - Setiawan, Heri; Aji, Styo Mahendra Wasita (Journal of Elementary Education, 2024)
The aim of writing this article is to analyze the various character values contained in game games. Therefore, in this paper we discuss the potential for implementing games to strengthen the character values of elementary school students. The method for writing this article uses a literature review. Various literature related to the topic of discussion, namely character education, traditional games, and various character values in traditional games. This step was carried out to review the curriculum, legal basis, and research literature from various open access journal sources such as Sinta, ERIC, Google Scholar and then analyzed and synthesized so that a study could be taken that formulated various potential character values in traditional games. The analysis results show that, as a traditional game, games also have various character values. The following describes some of the values contained in games, namely: cooperation, leadership, mutual respect, sportsmanship, responsibility, discipline (obeying the rules), economic values, and togetherness.